PENGARUH KOMISARIS INDEPENDEN DAN KOMITE AUDIT TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2021–2023 - Meri Yanti; Melisa Putri Iriani; Putri Alya Nabila (Komunitas Manajemen Kompetitif, 2026)
This study aims to examine the effect of independent commissioners and audit committees on the financial performance of food and beverage sector companies listed on the Indonesia Stock Exchange (IDX) for the 2021–2023 period. A causal-comparative quantitative approach with a ratio measurement scale was applied. Using purposive sampling, 40 companies were obtained with a total of 120 observations; after removing 6 extreme data points, the final sample was 114. Secondary data were collected through documentation from the IDX website and the companies' official websites, then processed using SPSS version 26. The results show that independent commissioners (X₁) have a significant negative effect on financial performance (t-value = -3.667; sig = 0.000), audit committees (X₂) have a significant negative effect on financial performance (t-value = -2.466; sig = 0.015), and simultaneously both variables have a significant positive effect on financial performance (F-value = 8.239 > F-table = 3.08; sig = 0.000). The Adjusted R Square value of 0.114 indicates that 11.4% of the variation in financial performance is explained by these two variables, while 88.6% is influenced by other factors outside the model.